I've got problem with such an example:

Given equation $\frac{dx}{dt} = -x + x^7$ with initial condition $x(0) = \lambda$, where $x=x(t, \lambda)$. Find $\frac{ \partial x(t, \lambda)}{\partial \lambda} \mid _{\lambda = 0}$.

What I've got now is:

We can write: $x(t, \lambda) = \int_{0}^{t} -x + x^7 ds + C(t,\lambda)$

but since $x(0) = \lambda$, we've got $\lambda = x(0, \lambda) = \int_{0}^{0} -x + x^7 ds + C(0,\lambda) = C(0, \lambda)$ and so $x(t, \lambda) = \lambda + \int_{0}^{t} -x + x^7 ds$

Now we can apply $\frac{ \partial }{\partial \lambda}$ to both sides getting: $\frac{ \partial x(t, \lambda)}{\partial \lambda} = 1 + \int_{0}^{t}{ \frac{ \partial}{\partial \lambda}(-x(t, \lambda)) + \frac{ \partial}{\partial \lambda}(x(t, \lambda)^7) }ds$. But now I have no idea how can I calculate value of that integral.

Does anyone have idea how to move further with that solution ? Or maybe that is wrong path and there exists easier way to solve that problem?

Thanks in advance for all the help

  • $\begingroup$ @robert-israel I get it how you've found $y(t, \lambda)$, but when I plug $\lambda=0$, nothing changes am I right ? I mean in $exp$ there will be only $0$ instead of $\lambda$. $\endgroup$
    – storaged
    Jun 30 '13 at 21:21
  • $\begingroup$ You can easily find $x(t,0)$. $\endgroup$ Jul 1 '13 at 6:55

Let $y(t,\lambda) = \dfrac{\partial}{\partial \lambda} x(t,\lambda)$. Differentiating the differential equation $ \dfrac{\partial x}{\partial t} = - x + x^7$ with respect to $\lambda$, we get $\dfrac{\partial y}{\partial t} = - y + 7 x^6 y$, with $y(0,\lambda) = 1$. Solving this linear homogeneous initial value problem for $y$, we get $$y(t,\lambda)) = \exp\left(\int_0^s (7 x(s,\lambda)^6 - 1)\ ds\right)$$ Now plug in $\lambda=0$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.